Discussions in dispute resolution : the foundational articles - Hinshaw, Art; Schneider, Andrea Kupfer; Cole, Sarah R. (New York, NY : Oxford University Press, 2021)
While arbitration was robust in colonial and early America, dispute resolution lost its footing to the court system as the United States grew into a bustling and burgeoning country. And while dispute resolution processes emerged briefly from time to time, they were dormant until the enactment of the Federal Arbitration Act and collective bargaining grew out of the labour movement. But it wasn't until 1976, when Frank Sander delivered his famous remarks at the Pound Conference, that the modern dispute resolution movement was born. By the year 2000, alternative dispute resolution had transformed from a populist rebellion against the judicial system to mainstream legal practice. Today, lawyers and retiring judges look to arbitration and mediation for a career pivot, and law schools train law students in the finer arts of dispute resolution practice as both providers and advocates.
Also issued in print: 2021.
Includes bibliographical references.
Specialized.
Description based on online resource; title from home page (viewed on May 21, 2021).
Keywords: Dispute resolution (Law) -- United States; Mediation -- United States; Arbitration and award -- United States; Negotiation -- United States; Dispute resolution (Law)